2018
DOI: 10.1002/adma.201870372
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Skyrmions: Current‐Induced Skyrmion Generation through Morphological Thermal Transitions in Chiral Ferromagnetic Heterostructures (Adv. Mater. 49/2018)

Abstract: Magnetic skyrmions are particle‐like chiral twists of the magnetization that promise advances in spin‐based data storage and logic device applications. In article number https://doi.org/10.1002/adma.201805461, Mathias Kläui, Geoffrey S. D. Beach, and co‐workers examine current‐induced generation of skyrmions in heavy‐metal/ferromagnet multilayers and show that Joule heat pulses can drive topological transitions in magnetic textures and enable skyrmion creation on nanosecond timescales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In 2016, Yuan and Wang theoretically demonstrated that a skyrmion can be created in a ferromagnetic nanodisk by applying a nano-second current pulse (j ~ 2.0 × 10 12 A m −2 ) [186]. Yin et al also suggested in a theoretical study that it [33], which turned out to be thermally-induced skyrmion generation as systematically studied recently by Lemesh et al [34]. Hrabec et al also reported the experimental creation of skyrmions induced by applying electric current (j ~ 2.8 × 10 11 A m −2 ) through an electric contact placed upon a symmetric magnetic bilayer Reprinted with permission from [198].…”
Section: Spin-polarized Electric Currentmentioning
confidence: 94%
See 2 more Smart Citations
“…In 2016, Yuan and Wang theoretically demonstrated that a skyrmion can be created in a ferromagnetic nanodisk by applying a nano-second current pulse (j ~ 2.0 × 10 12 A m −2 ) [186]. Yin et al also suggested in a theoretical study that it [33], which turned out to be thermally-induced skyrmion generation as systematically studied recently by Lemesh et al [34]. Hrabec et al also reported the experimental creation of skyrmions induced by applying electric current (j ~ 2.8 × 10 11 A m −2 ) through an electric contact placed upon a symmetric magnetic bilayer Reprinted with permission from [198].…”
Section: Spin-polarized Electric Currentmentioning
confidence: 94%
“…These topologically non-trivial spin textures can be one-dimensional (1D), two-dimensional (2D) and three-dimensional (3D) in real space, and usually carry integer or half-integer topological charges determined by their spin textures in the topological space . For most cases, the well-studied topological spin textures are those localized in 2D or quasi-2D magnetic thin films and multilayers [11,19,21,[23][24][25][26][27][28][29][30][31][32][33][34][35][36], because that magnetic thin films and multilayers are better understood and preferred for building nanoscale spintronic applications. Several recent works have also demonstrated promising properties of 3D topological spin textures [10,[37][38][39][40][41][42][43][44][45][46][47][48][49][50], leading to the prediction that 3D spin textures might be used in combination with 2D textures in the future.…”
Section: Topological Spin Texturesmentioning
confidence: 99%
See 1 more Smart Citation